Warm Compresses on Reducing the Intensity of the Pain Scale in Parting Women - Emi Sutrisminah; Endang Surani; Aina Nurus Syofa (Sarana Ilmu Indonesia (salnesia), 2023)
Labor is the process of opening and thinning the cervix and the fetus will descend into the birth canal. Normal delivery care is clean and safe care during labor until the baby is born, as an effort to prevent complications, especially post-natal bleeding, hypothermia and newborn asphyxia. During the first active phase of labor, there is a descent of the lowest part of the fetus into the pelvic cavity which causes pain due to contractions, where pain management is needed. Non-pharmacological methods of reducing pain in women in labor can be done, one of which is by giving warm compresses. This study aimed to determine the effect of giving warm compresses on back pain in women giving birth during the first active phase. This research design used a Quasy Experiment with a Non-Equivalent Control Group design. The research subjects were 30 mothers giving birth during one active phase, taken by accidental sampling. The instrument used was a pain scale observation sheet which was analyzed using the paired t-test. The results study showed there was an effect of warm compresses on back pain in women giving birth during the first active phase with a p-value=0,000 (p-value?0,05). Based on the research results above, can be concluded that gived a warm compress using a belt can reduce back pain in mothers during labor during the active phase of labor.